2015
DOI: 10.5665/sleep.4664
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Vulnerability to Sleep Deprivation Using Baseline Measures of Psychomotor Vigilance

Abstract: Despite differences in experimental conditions across studies, drift diffusion model parameters associated reliably with individual differences in performance during total sleep deprivation. These results demonstrate the utility of drift diffusion modeling of baseline performance in estimating vulnerability to psychomotor vigilance decline following sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…They approach the problem by assessing a person’s responses to sleep deprivation periodically and updating the model to predict his/her responses to subsequent sleep deprivation, rendering it an impractical approach for many situations. More recently, drift diffusion model 53 parameters derived from baseline PVT data have been used to classify participants in resilient and vulnerable groups with 77% accuracy using a support vector machine (SVM) modeling approach 18 . In its current form, however, that model requires data to be combined across consecutive PVTs for reliable estimates of drift diffusion parameters, whereas our classifier relies on data derived from a single 10-min PVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They approach the problem by assessing a person’s responses to sleep deprivation periodically and updating the model to predict his/her responses to subsequent sleep deprivation, rendering it an impractical approach for many situations. More recently, drift diffusion model 53 parameters derived from baseline PVT data have been used to classify participants in resilient and vulnerable groups with 77% accuracy using a support vector machine (SVM) modeling approach 18 . In its current form, however, that model requires data to be combined across consecutive PVTs for reliable estimates of drift diffusion parameters, whereas our classifier relies on data derived from a single 10-min PVT.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that sleep deprivation can amplify individual differences in PVT performance that were already present at baseline. Moreover, these studies suggest that baseline measures of PVT performance can potentially be used to improve predictions of individual differences in attentional responses to sleep deprivation 18 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 Even so, it has been reported that baseline diffusion model drift rate can be used to predict PVT performance during total sleep deprivation (Patanaik et al, 2015). …”
mentioning
confidence: 99%
“…Repeated measures ANOVA, using multivariate models, with resistant/vulnerable cognitive performance as a between-participants factor was used to assess ESB and ISB measures across the five time points. Cognitively resistant (n = 8) and cognitively vulnerable (n = 8) groups were defined by a median split on TSD 10-min PVT performance [66], defined by total lapses (>500 ms response time) and errors performance (range: 1.33-33.33 PVT lapses and errors; mean ± SD, resistant: 3.63 ± 2.15 PVT lapses and errors; vulnerable: 12.00 ± 8.71 PVT lapses and errors); these groups were not significantly different in terms of sex or age (p > .05). After ANOVAs, post hoc comparisons corrected for multiple testing were used to assess differences in ESB and ISB measures for the cognitively resistant versus cognitively vulnerable groups at each time point.…”
Section: Statistical Analysesmentioning
confidence: 99%